The Influence of Female Chief Executive Officer and Female Chief Financial Officer on Earnings Management in Manufacturing Companies in The Consumption Goods Industry Sector Registered on the BEI in 2021-2022 - Sakiah Maisaroh; Nidia Anggreni Das; Rita Dwi Putri (Basic and Applied Accounting Research Journal, 2024)
This research aims to analyze the influence of Female CEO and Female CFO on Earning Management. This research was conducted on consumer goods industrial sector companies listed on the IDX in 2021-2022, the sample was selected using a purposive sampling method and the data that passed the selection were 36 companies. The research results show that Female CEO (X1) has no significant effect on Earnings Management (Y). This is proven by using the t-value of 0.287 < t table 1.996 and a significant value of 0.775 > 0.05. Female CFO (X2) has no significant effect on Earnings Management (Y). This was proven using the t-value of |0.284| < ttable 1.996 and a significant value of 0.777 > 0.05. After that, Female CEO (X1) and Female CFO (X2) do not simultaneously influence Earning Management (Y). This result is proven by the F-value of 0.076 < Ftable and a significant value of 0.973 > 0.05